New Trends of Literacy Transformation’s Values of Religious Education in Digital Era - Mildasari, Dina Aulia; Mujab, Muhammad (Proceeding International Conference on Religion, Science and Education, 2024)
The digital era can be an opportunity and a challenge for teachers, if teachers can make use of online sources that can be used by students for their reading, According Najwa Shihab’s statement about the challenges faced of digital literacy are data awareness, the ability to analyze data and the ability to focus. According to the Ministry of Education and Culture in 2019, the average reading index in Indonesia is low, at 37.32 percent. Literacy value means values that needed for reading and writing. This is supported by Ertem, stated that "Reading activities are cognitive activities, and interactions that involve the reader and text that build an understanding". Literacy today is not just the ability to read and write but how a student can understand digital information. With this, it is hoped that teachers can innovate to make classes fun that will be easier to understand the concepts of religious learning as a whole. This research aims (1) To explore how teachers integrate religious education with digital literacy, (2) To describe the challenges and opportunities religious education in digital era. This research employs a descriptive qualitative research method. Qualitative research, research that emphasizes the aspect of in-depth understanding of a problem in addition to looking at problem for generalization research. The data collection techniques used were interviews, observations, and documentation. Data analysis consist of three streams of activities that occur simultaneously such as data reduction, data presentation, conclusion withdrawal, and verification. Efforts to check the validity of the data using triangulation techniques, such as comparing the results of the research obtained, as well as persistence of observation. The results indicate that there is recent trend in this digital era that can be used by Religious teachers to encourage students’ literacy online skills.